Cartilage rehydration: The sliding-induced hydrodynamic triggering mechanism. (15th April 2021) - Putignano, Carmine; Burris, David; Moore, Axel; Dini, Daniele
Graphical abstract: Abstract: Loading-induced cartilage exudation causes loss of fluid from the tissue, joint space thinning and, in a long term prospective, the insurgence of osteoarthritis. Fortunately, experiments show that joints recover interstitial fluid and thicken during articulation after static loading, thus reversing the exudation process. Here, we provide the first original theoretical explanation to this crucial phenomenon, by implementing a numerical model capable of accounting for the multiscale porous lubrication occurring in joints. We prove that sliding-induced rehydration occurs because of hydrodynamic reasons and is specifically related to a wedge effect at the contact inlet. Furthermore, numerically predicted rehydration rates are consistent with experimentally measured rates and corroborate the robustness of the model here proposed. The paper provides key information, in terms of fundamental lubrication multiscale mechanisms, to understand the rehydration of cartilage and, more generally, of any biological tissue exhibiting a significant porosity: such a theoretical framework is, thus, crucial to inform the design of new effective cartilage-mimicking biomaterials. Statement of significance: Motion and, precisely, joints articulation ensures that cartilage tissues preserve adequate level of hydration and, thus, maintain excellent mechanical properties in terms of high resilience, considerable load-carrying capacity and remarkably low friction. Conversely, when statically loaded, cartilage starts to exudate, causing joint space thinning and, in the long term, possible osteoarthritis; joints motion is, thus, the key to prevent the degradation of the tissues. By developing a numerical multiscale lubrication theory, and by corroborating this approach with experiments, we provide the first original theoretical explanation to this motion-induced cartilage rehydration mechanism. Assessing the rehydration hydrodynamic origin is, in fact, fundamental not only to understand the joints physiology, but also to highlight a key requirement for cartilage-mimicking biomaterials.